Brazilian adaptation of the driving anger expression inventory: testing its psychometrics properties and links between anger behavior, risky behavior, sensation seeking, and hostility in a sample of Brazilian undergraduate students. (September 2019) - Olandoski, Guilherme; Bianchi, Alessandra; Delhomme, Patricia
Abstract: Introduction : In Brazil, driver aggressiveness in road traffic is a critical issue and could be an important contributing factor to the high number of traffic accidents. Because no instruments are available in Portuguese to register driving aggressiveness or driving anger in Brazil, we adapted English instruments into the Brazilian context. The aims of this study were to provide a Brazilian adaptation of the Driving Anger Expression Inventory (DAX) and to try to validate it by testing its psychometric properties and investigating its relationships with risky driving behaviors (DBQ), road accidents, driving sensation seeking, and hostility. Method : The Brazilian adaptations of the DAX, DBQ, the Driving Sensation Seeking Scale (DSSS) and the hostility Scale were administered to a sample of 512 undergraduate students (with a mean age of 23.7 years, 52.1% men). Results : Confirmatory factor analysis of the Brazilian DAX (DAX-BR) items yielded a four-factor solution with 43 items, which obtained the best goodness-of-fit to the data. Cronbach's alpha for the DAX-BR factors ranged from 0.69 to 0.88. Other results on validity were a positive correlation (range 0.39–0.59) between the factors of the DAX-BR, DSSS, and DBQ. Conclusion : DAX-BR as the same structure as the original and is a reliable instrument for use with young drivers. Other studies should be conducted to further validate the DAX-BR in different types of populations such as older and more experienced drivers, professional drivers, and traffic regulation offenders whose driver's license has been taken away. Practical applications: This Brazilian version can be recommended for the assessment of driving anger expression in Brazil among young drivers in view of helping them driver more safely, and in particular to reduce traffic violations. Highlights: The study provides evidence of the validity of the Brazilian adaptation of the Driving Anger Expression Inventory - (DAX-BR). The structure of the factors for the DAX-BR was similar to the original one. DAX-BR has good psychometric properties. Results showed that the DAX-BR is a good predictor of the DBQ scales. DAX-BR can be recommended for the assessment of driving anger expression in Brazil among young drivers.